A Short and Convenient Synthesis of closo‐Dodecaborate Sugar Conjugates. Issue 43 (8th November 2019) - Imperio, Daniela; Muz, Barbara; Azab, Abdel Kareem; Fallarini, Silvia; Lombardi, Grazia; Panza, Luigi
Abstract : Dodecaborate anions represent a suitable boron source for boron neutron capture therapy (BNCT). Sugar derivatives of dodecaborate have been prepared through the ring‐opening reaction of cyclic oxonium ions by alkoxide nucleophiles. According to this general approach, a convenient and short synthesis of three derivatives of dodecaborate‐sugar conjugates is herein reported. Glucose, galactose and fructose have been chosen for their expected preferential uptake by tumor cells compared to healthy cells. The free hydroxyl group of isopropylidene protected sugars was exploited as nucleophile to open a dodecaborate cyclic oxonium salt, giving products containing a spacer between the sugar and the boron cluster. Deprotection of the sugar moiety in acidic conditions gave the desired compounds in excellent yield. Abstract : Sugar derivatives of closo ‐dodecaborate with glucose, galactose and fructose have been prepared through the ring‐opening reaction of cyclic oxonium ions by alkoxide nucleophiles as potential agents for boron neutron capture therapy (BNCT) through a convenient and short synthesis. The final compounds were tested for toxicity and cellular uptake.